MOLECULAR GENETIC DETECTION OF BACTERIAL VAGINOSIS AT KAZAKHWOMEN IN REPRODUCTIVE AGE - Oradova, Axoltan; Duyssembayev, Bilimzhan (European Scientific Journal, ESJ, 2014)
Introduction: The diagnostic of sexually transmitted infection (STI) sharply increased. Steady growth of STI at persons of young age, women of fertility age who are often accompanied by the complications leading to disability, to infertility, a pre-natal infection is observed, causing fruit and newborn diseases. The purpose of our study was to analyze the molecular genetic detection of bacterial vaginosis at women in reproductive age by noninvasive methods. Materials and Methods: Total DNA was isolated was extracted from vaginal samples at 54 women between the ages of 15 and 45 years who were able and willing to give informed consent. The analysis of products of PCR of amplification carried out by PCR in real time. Results: It is revealed that associations bacterial vaginosis less often met three infectious agents in comparison with one and two (18, 5±3, 5 %, 38,9±6,3 %, 42,6±6,5 %, respectively, (р<0,05). Conclusion: Our study demonstrates that, using a panel of DNA by means of PCR in real time the identification of BV patients with minimally invasive techniques.